2023
DOI: 10.1002/jbt.23549
|View full text |Cite
|
Sign up to set email alerts
|

Glycyrrhizin protects against diosbulbin B‐induced hepatotoxicity by inhibiting the metabolic activation of diosbulbin B

Bufan Yang,
Jie Liu,
Xiaojin Chang
et al.

Abstract: Diosbulbin B (DIOB), isolated from herbal medicine Dioscorea bulbifera L. (DB), could induce severe liver injury, and its toxicology was closely associated with CYP3A4‐mediated metabolic oxidation of furan moiety to the corresponding cis‐enedial reactive metabolite. Glycyrrhizin (GL), the major bioactive ingredient in licorice, can inhibit the activity of CYP3A4. Thus, GL may ameliorate hepatotoxicity of DIOB when GL and DIOB are co‐administrated. The study aimed to investigate the protective effect of GL on D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…Yang and colleagues reported that glycyrrhizin was hepatoprotective in a mouse model when administered with diosbulbin B (DIOB), the purported component of Dioscorea bulbifera L. responsible for liver injury [96]. This herbal agent is used for the treatment of thyroid disorders in China and has been associated with severe liver injury, which has limited its use [97].…”
Section: Corticosteroids With Glycyrrhizinmentioning
confidence: 99%
“…Yang and colleagues reported that glycyrrhizin was hepatoprotective in a mouse model when administered with diosbulbin B (DIOB), the purported component of Dioscorea bulbifera L. responsible for liver injury [96]. This herbal agent is used for the treatment of thyroid disorders in China and has been associated with severe liver injury, which has limited its use [97].…”
Section: Corticosteroids With Glycyrrhizinmentioning
confidence: 99%